A Review on Biomass for Electricity Generation in Indonesia - Primadita, Dony Septa; Kumara, I.N.S.; Ariastina, W.G. (Journal of Electrical, Electronics and Informatics; Vol 4 No 1 (2020): JEEI (February 2020), 2020)
The Indonesian National Energy Policy stipulates that renewable energy must contribute 23% of total energy consumption by 2025 and increase to 31% by 2050. Among many resources of the country, biomass is a renewable energy source whit the potential is estimated at 32,654 MW. This article reviews the biomass and electricity generation implementation in Indonesia to get insights on the development of the biomass for power generation of the country. Currently, the biomass electricity generation technology that has been applied in Indonesia includes direct combustion as fuel for coal power plants or co-firing, converted into refuse-derived fuel, gasification, sanitary landfills, and incinerators. From 2011 to 2019, the installed capacity of biomass power plants reached 1857.5 MW or 33.78% of the target of 5500 MW in 2025. The biomass power plants are located in North Sumatra, Jambi, Gorontalo, Riau, West Nusa Tenggara, Papua, Bangka Belitung, North Sulawesi, South Sumatra, East Java, and Jakarta. Considering the high 2025 electricity from biomass target, it is necessary to develop a more intensive biomass power plants because of its large potential, available technology, and its benefits to increase the electrification ratio especially for providing electricity for people in areas not yet covered by the utility network, realizing national energy security, and reducing the use of fossil-based fuels.